THE INNOVATIVENESS OF THE SERVICE SECTOR IN THE EUROPEAN UNION COUNTRIES - Decyk, Kamil (Management and Administration Journal, 2020)
The subject of innovativeness is an interesting and unusually up-to-date research area in Poland and other countries. It is especially interesting to consider the situation in the service sector, whose specific character is largely related to the non-technological scope of innovativeness. With regards to such an outline of the research, the objective of this paper is to evaluate the level of the innovativeness of the service sector in EU countries. The research material in the paper was the Eurostat prepared database regarding the following: the level and type of innovative activity, as well as the degree of innovation in the EU services sector. In order to obtain the research goal, the method of analysis and criticism of literature, comparative analysis was used and the arithmetic mean was used to determine the levels of innovation. Based on the conducted research the top innovative level service sector countries include: France, the Netherlands, Italy, Spain and the United Kingdom. The medium level countries include: Germany, Sweden, Portugal and Poland. The service sectors of other countries were classified as low level innovativeness. The research, did not identify the influence of the service sector innovativeness on the innovativeness level of particular countries